2017
DOI: 10.23887/ijll.v1i3.12544
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Big Book as Media on Students’ Reading Comprehension at Fifth Grade of Elementary School

Abstract: This study was aimed at investigating whether or not there was a significant effect of the implementation of Big Book as media on reading comprehension achievement of the fifth grade students. This study was conducted in SD Laboratorium Undiksha Singaraja in the form of an experimental research with post-Test only Control Group Design. The population was the fifth grade in which two classes were selected as the sample of the study. Then, the samples were decided as the experimental group and control group by u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 3 publications
3
10
0
3
Order By: Relevance
“…The result was all children had a good improvement in their reading readiness by using Big Book. Moreover, this current study was also in line with Mahayanti, Artini, & Jannah ( 2017) who conducted research entitled The Effect of Big Book as Media on Students" Reading Comprehension at Fifth Grade of Elementary School in SD Laboratorium Undiksha Singaraja. The result of this research showed that there was a significant difference of reading comprehension achievement between students treated by using Big Book as media and those treated by using conventional media.…”
supporting
confidence: 71%
“…The result was all children had a good improvement in their reading readiness by using Big Book. Moreover, this current study was also in line with Mahayanti, Artini, & Jannah ( 2017) who conducted research entitled The Effect of Big Book as Media on Students" Reading Comprehension at Fifth Grade of Elementary School in SD Laboratorium Undiksha Singaraja. The result of this research showed that there was a significant difference of reading comprehension achievement between students treated by using Big Book as media and those treated by using conventional media.…”
supporting
confidence: 71%
“…Furthermore, this current study was also in line with three studies. First, Mahayanti, Padmadewi, and Wijayanti (2017) who found that there was a significant effect of Big Book as media on students" reading comprehension at fourth grade of elementary school. Second, Mahayanti, Artini, and Jannah (2017) who found that there was a significant difference of reading comprehension achievement between students treated with Big Book as media and those treated using conventional media at fifth grade of elementary school.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Salah satu media pembelajaran yang bisa digunakan untuk tujuan literasi dwibahasa ini adalah big book. Big book merupakan sebuah buku besar dengan cerita dan ilustrasi menarik bagi anak (Colville-Hall & O'Connor, 2006;Mahayanti et al, 2017). Colville-Hall & O'Connor (2006) merinci bahwa maksimal big book hanya sebanyak 15 halaman, berisi cerita sederhana namun menarik, dengan beberapa kosakata yang terulang.…”
Section: Pendahuluanunclassified